The role of the manager-facilitator of the clustering in health care - Mirković, Irena (PONS - medicinski časopis, 2016)
Apstract: Cluster managers, cluster fasilitators and cluster organizations of health play decisive, a vital role making management, transformation and revitalization for every members of cluster. They should act as agents of changes,the need for change and promotive innovative models, cooperations among partners a exchange to apply knowledge, and models at in nations,regionals,european regulations. Conclusion: A cluster facilitator is a recognition to new job profile in managing the clusters. The role managers fasilitators in proces of clustering in health institutions, has vital at apply knowledge, in care successful of health system. Besides ,characteristic managers fasilitator had in corsponding a rise and the standardisation of health system institutions in world with high a regulations the global economy trends. Key words: cluster,cluster managers, cluster managers- fasilitators, clustering proces, innovative cooperations,medical institutions,health institutions